The Propositional and Expressive Meanings Transfer in English to Indonesian Sexual Slang Translation - Yuwono, Albertus Agung (Universitas Pahlawan Tuanku Tambusai, 2024)
To translate sexual slang from English to Indonesian, one must comprehensively understand both languages' propositional and expressive meanings. The transfer of the meanings is crucial in determining the accuracy and acceptability of the translation. This study aims to categorize sexual slang based on its propositional meaning, analyze the translation strategies of transferring the propositional and expressive meanings, and assess the impacts of the strategies on the accuracy and acceptability of the translation. This study utilizes descriptive-qualitative methods and applies total and purposive sample approaches to gather data from the English dialogue of The Guru movie and its Indonesian subtitles. This research demonstrates the translation strategy achieving a high level of accuracy involves words or phrases with similar propositional and expressive meanings. In contrast, the translation strategy with a high level of acceptability involves words or phrases with similar propositional but less expressive meanings.